Red right hand [videorecording (DVD)] - Easley, Jonathan; Dillahunt, Garret, 1964-; Bloom, Orlando, 1977-; MacDowell, Andie; Lafferty, James, 1985-; Geraghty, Brian; Logan, Nicholas; Park, Alexandra, 1989-; Ratchford, Jeremy (Magnolia Home Entertainment, 2024)
Cash is trying to live an honest and quiet life taking care of his recently orphaned niece Savannah in the Appalachian town of Odim County. When the sadistic kingpin Big Cat, who runs the town, forces him back into her services, Cash learns he's capable of anything, even killing, to protect the town and the only family he has left. As the journey gets harder, Cash is drawn into a nightmare that blurs the lines between good and evil